Analisis Peran Pasar Tradisional Arba Terhadap Pendapatan Pedagang di Kecamatan Anjir Pasar Kabupaten Barito Kuala - Fahlinawati, Wiwin; Nasrudin, Nasrudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
Research is located in the Arba market which is a traditional market. Various kinds of traders gather at the Arba Market such as vegetable, fish, fruit, market snacks and clothing traders who operate every Wednesday. Using primary and secondary data a qualitative descriptive method which aims to determine the extent of the part of the Arba traditional market in income of market traders and impact of the income of these traders on their household life in Anjir Pasar sub-district, Barito Kuala district. The results of the study show that the Arba market plays a role in increasing the economic income of traders. This can be seen from the large number of people who buy and sell in the market for their daily needs that they can improve their standard of living such as buying transportation, paying for education to having personal savings.